Classification of Crangonyx islandicus (Amphipoda, Crangonyctidae) based on morphological characters and comparison with molecular phylogenies - KORNOBIS, ETIENNE; PÁLSSON, SNÆBJÖRN; SVAVARSSON, JÖRUNDUR (Zootaxa, 2012)
Crangonyx islandicus is a groundwater amphipod species endemic to Iceland and a member of the family Crangonyctidaewhich is widespread throughout the Holarctic region. A previous study based on variation in nuclear genes showed thatC. islandicus closest relatives are Crangonyx species from North America, where most of the species diversity of the genusoccurs. In this study, we aim at describing the morphological affinities of C. islandicus with North American Crangonyxspecies and two Eurasian species, C. chlebnikovi and C. subterraneus. We used the morphological characters defined byZhang & Holsinger (2003) and scored them for different populations of C. islandicus as well as for C. chlebnikovi and C.subterraneus. The molecular phylogeny of the Crangonyctidae family and the morphological character states are com-pared in order to detect potential convergence in the morphological traits, common in subterranean species. C. islandicusappears to be close morphologically to C. subterraneus from Europe and C. longicarpus from North America. The morphological proximity of C. islandicus and C. subterraneus is incongruent with the pattern observed from molecular data.